What God only knows: a reply to Rob Lovering. Issue 2 (25th October 2013) - FRISE, MATTHEW
Abstract Rob Lovering has recently argued that God is not omniscient on the grounds that (1) in order to be omniscient a subject must not only know all truths always but also know what it's like not to know a truth, and (2) God cannot fulfil both of these requirements. I show that Lovering's argument is unsuccessful since he inadequately supports (1) and (2), and since there are several serious doubts about (2). I also show that Lovering does not otherwise indicate that God is not maximally great.